2010
DOI: 10.1111/j.1538-7836.2010.03981.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory management of pulmonary embolism: a pragmatic evaluation

Abstract: Summary. Background:Patients diagnosed with pulmonary embolism should be considered for treatment on an outpatient basis; however, this practise is not accepted in many centers. Objectives: Review the safety and efficacy of ambulatory management of patients with pulmonary embolism at our institution. Patients/Methods: This was a retrospective single center cohort study of consecutive patients diagnosed with idiopathic or secondary pulmonary embolism between January 2003 and January 2008 at the London Health Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 32 publications
4
35
0
3
Order By: Relevance
“…The other retrospective study by KOVACS et al [5] did not give information on the clinical outcomes of patients treated in the hospital. The rates of adverse clinical outcome in the outpatient group are comparable with the rates in the Hestia study: none of the patients treated at home died of fatal PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other retrospective study by KOVACS et al [5] did not give information on the clinical outcomes of patients treated in the hospital. The rates of adverse clinical outcome in the outpatient group are comparable with the rates in the Hestia study: none of the patients treated at home died of fatal PE.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, two retrospective studies on outpatient treatment of PE were published [4,5]. The Hestia study is an important prospective validation of these retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that outpatient management or early discharge of patients with acute PE is safe and effective [8][9][10][11][12][13]. Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Three recent cohort studies have demonstrated that selecting PE patients for outpatient treatment solely on a clinical basis, primarily focusing on hemodynamic stable PE patients who do not require an oxygen supply, yields safe results in terms of low risks of recurrent VTE and mortality [9][10][11]. Given that patients with an asymptomatic PE are clearly able to compensate for the hemodynamic and respiratory consequences of the PE and unlikely to have decreased right ventricular function, these patients may be deemed good candidates for outpatient management, in particular if a PE is detected on elective CT scans in an outpatient setting.…”
mentioning
confidence: 99%